Does ESG Risk Rating Matter for Firm Value in Indonesia? Testing the Interaction Effect of Firm Size: JEL Classification: G30, G32, G34 - Natalia, Evy; Santoso, Hadi; Hartono`, Hartono (Journal La Bisecoman, 2025)
This study aims to analyze the impact of ESG Risk Rating, profitability, and growth opportunity on firm value. Given the ongoing debates surrounding ESG research in Indonesia, a more in-depth examination is required. The researcher has developed three econometric models to test six hypotheses related to this issue. This research is distinct from previous studies as it proposes an integrated model incorporating firm size as a moderating variable. The estimation model was tested using moderated regression analysis (MRA), with data comprising 240 observations over the period 2019-2024. The analysis results indicate that ESG Risk Rating in Indonesia does not have a significant impact on firm value. However, profitability and growth opportunity exhibit a significant positive effect on firm value. Further, the interaction model analysis reveals that firm size moderates the relationship between growth opportunity and firm value. These findings suggest that, at present, ESG Risk Rating information in Indonesia is not considered relevant by investors in assessing corporate performance.